Comparative Advantages of Public Loan and Public Equity Schemes in Venture Capital Markets - Andrea Schertler (Kiel Institute for World Economics (IfW), 2002)
Using an agency framework, this paper examines advantages of offering venture capitalists a choice between public equity and loan schemes. Both schemes can be used to promote venture capital investments in hightechnology enterprises since they encourage inexperienced venture capitalists to accumulate experience. However, under both schemes, experienced venture capitalists save on management support. This paper shows that offering venture capitalists a choice between these two schemes can lead to a positive self-selection. Inexperienced venture capitalists choose public equity under which they have higher incentives to enter the market. Experienced venture capitalists choose public loans under which they have lower incentives to save on their management support.
Keywords: L14; G28; G24; D82; 330; public equity schemes; public loan schemes; venture capital; Risikokapital; Öffentliche Kapitalbeteiligung; Öffentliche Kreditvergabe; Subvention; Unternehmensgründung; Finanzierungstheorie; Agency Theory; Theorie; Deutschland